2019
DOI: 10.3390/su11185107
|View full text |Cite
|
Sign up to set email alerts
|

The Technical Efficiency of French Regional Airports and Low-Cost Carrier Terminals

Abstract: In France, the regional airport’s demand for services is facing challenges due to the continuous expansion of the high-speed train, high-speed line, and highway networks. This study focuses on the viability of regional airports in France through technical efficiency using data envelopment, principle component analysis, Malmquist productivity index, and regression analysis using bootstrapping. To face the current competitive environment, the regional airports in France adopted strategies, such as the constructi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Among the numerous studies focusing on the antecedents of CoPS innovation, the compatibility of the technologies and functions across modules [16], with the underlying coordination effort made by the integrator to work jointly with its various key suppliers, is the far more fundamental and critical factor that contributes to the success of CoPS innovation, especially in the CoPS context of highly interdependent tasks and closely coupled technologies [18]. In this vein, the lean [19][20][21] and agile [22,23] manufacturing practices share the same core dimension as coordination with CoPS innovation in improving the efficiency of productive and innovative activities.…”
Section: Integrator's Coordination In the Context Of Cops Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the numerous studies focusing on the antecedents of CoPS innovation, the compatibility of the technologies and functions across modules [16], with the underlying coordination effort made by the integrator to work jointly with its various key suppliers, is the far more fundamental and critical factor that contributes to the success of CoPS innovation, especially in the CoPS context of highly interdependent tasks and closely coupled technologies [18]. In this vein, the lean [19][20][21] and agile [22,23] manufacturing practices share the same core dimension as coordination with CoPS innovation in improving the efficiency of productive and innovative activities.…”
Section: Integrator's Coordination In the Context Of Cops Innovationmentioning
confidence: 99%
“…While the integrator's coordination might be important to other industries too, their role in CoPS sectors is critical and irreplaceable [7]. In addition, while existing studies on new production innovation [12], innovation network [8,14], organization structure [4], lean [19][20][21] and agile [22,23] manufacturing and alliance management [16,30,59] have mainly emphasized the benefits of coordination in inter-organizational collaboration, under more complex context, higher level of coordinated activities are required to process the whole project smoothly [12]. It is exactly the case in the extreme complex context of CoPS innovation where the integrator shoulders the main responsibility for the coordinated activities.…”
Section: Theoretical Contributionmentioning
confidence: 99%
“…Moreover, the aeronautical market has changed in recent years with the appearance of low-cost carriers (LCC), which enables direct flights between small cities and large cities at competitive prices for a small number of potential users; the existence of significant scope for exploiting better connections in the intra-European markets for LCC has been proved [94]. It has been proved how the substantial increase in LLCs after the integration of Europe has provided an extensive boost in demand to/from foreign countries for regional airports in the whole continent [95][96][97]. In addition, in the British Isles, with a strong airport density, the development of an LCC network has proved that no matter whether a regional airport operates as an origin or destination gateway, notable improvements in the accessibility linked to these nodes can play a significant role in economic and/or tourism development [98].…”
Section: The Airportmentioning
confidence: 99%
“…While estimating an organization's performance, several studies [20,21] claimed that a multifactor performance assessment model should be developed, because 'performance' is a complex indicator requiring more than just any single measure to depict it. Hong and Jeon [22] further indicated that efficiency is equivalent to performance, and they used the data envelopment analysis (DEA) model to assess efficiency scores to reflect the business value creation process. As corporate sustainability is generally defined as a business approach to create long-term shareholder value with the limited resources, Lo [23] further presents that an organization's sustainability in terms of generating profit and attracting more investors has not been investigated a great deal.…”
Section: Introductionmentioning
confidence: 99%